Electrospun oriented gelatin‐hydroxyapatite fiber scaffolds for bone tissue engineering. Issue 7 (3rd April 2017) - Salifu, Ali A.; Lekakou, Constantina; Labeed, Fatima H.
Abstract: Tissue engineering of human fetal osteoblast cells was investigated on gelatin‐hydroxyapatite (HA), crosslinked, electrospun oriented fiber scaffolds at the different HA concentrations of 0, 10, 20, and 25 wt % in the dry fibers and different fiber diameter, pore size and porosity of scaffolds. Rheological tests and proton nuclear magnetic resonance spectroscopy were conducted for all solutions used for electrospinning. It was found that 25 wt % HA‐gelatin scaffolds electrospun at 20 kV led to the greatest cell attachment, cell proliferation and extracellular matrix (ECM) production while fiber orientation improved the mechanical properties, where crosslinked electrospun 25 wt % HA‐gelatin fiber scaffolds yielded a Young's modulus in the range of 0.5–0.9 GPa and a tensile strength in the range of 4–10 MPa in the fiber direction for an applied voltage of 20–30 kV, respectively, in the electrospinning of scaffolds. Biological characterization of cell seeded scaffolds yielded the rate of cell growth and ECM (collagen and calcium) production by the cells as a function of time; it included cell seeding efficiency tests, alamar blue cell proliferation assay, alkaline phosphate (ALP) assay, collagen assay, calcium colorimetric assay, fluorescence microscopy for live and dead cells, and scanning electron microscopy for cell culture from 1 to 18 days. After 18 days, cells seeded and grown on the 25 wt % HA‐gelatin scaffold, electrospun at 20 kV, reached production of collagen at 370 μg/L and calcium production at 0.8 m M . © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 1911–1926, 2017.